Analisa Environmental Jalan Raya untuk Estetika Suasana dan Manfaat pada Lingkungan Serta Bagi Pengguna - M Wahyu Dinarta; Marwan Lubis; M. Husni Malik Hasibuan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The road environment not only influences the physical aspects of a city but also significantly impacts the psychological state of road users. This study aims to explore the relationship between road infrastructure such as sidewalk design, lighting, and signage, with perceptions of urban aesthetics and road psychology within the context of detailed urban development. Qualitative research methods were employed, including field observations, in-depth interviews, and document analysis, to assess how these factors affect the behaviors and feelings of road users and surrounding residents. Findings indicate that well-designed road infrastructure can enhance feelings of safety, comfort, and visual satisfaction among road users, whereas poor integration may lead to stress and discomfort. The implications of this research underscore the importance of considering psychological aspects in the planning and development of detailed urban environments to create road environments that are not only functional but also support the psychological well-being of the community.